Vegetation condition and tourism suitability of natural mangrove in Bagek Kembar, Lombok, Indonesia - GITO HADIPRAYITNO; I WAYAN SUANA; DIDIK SANTOSO; LALU JAPA; ENI SUYANTRI; GDE CAHYADI WIRAJAGAT; MUHAMMAD SYAZALI; MOHAMMAD LIWA ILHAMDI; RIZKY REGINA KAWIRIAN (Society for Indonesian Biodiversity, 2024)
Abstract. Hadiprayitno G, Suana IW, Santoso D, Japa L, Suyantri E, Wirajagat GC, Syazali M, Ilhamdi ML, Kawirian RR. 2024. Vegetation condition and tourism suitability of natural mangrove in Bagek Kembar, Lombok, Indonesia. Biodiversitas 25: 3703-3711. The Bagek Kembar Essential Ecosystem area is one of several mangrove-based tourist destinations in Lombok, Indonesia. This area features a natural mangrove forest zone amidst rehabilitated mangrove forests from former community ponds. This study aimed to understand the vegetation structure and composition of natural mangrove, the level of damage and their suitability for ecotourism. Data were collected from March to May 2023 by establishing eleven research transects. Trunk diameter and tree height were measured and canopy cover was analyzed using the Hemispherical Photography Method. A vegetation analysis was used to describe the mangrove community structure and composition. Level of damage was assessed using density and coverage parameters of mangrove vegetation while suitability for tourism was assessed using the tourism suitability index with parameters including the number of species, density and thickness of mangroves, tides, and fauna associated with the mangrove ecosystem. Eight mangrove species from five families were identified with the dominance of three species: Avicennia marina (Forssk.) Vierh., Rhizophora mucronata Lam., and Rhizophora stylosa Griffith which spread across all transects. High variations in stem diameter and height indicated that the mangroves originated from natural succession. The natural mangrove forest zone in Bagek Kembar Essential Ecosystem area is classified as good based on the average density and percentage of canopy cover and is deemed very suitable for ecotourism development.